THE IMPACT OF SOME VARIABLES TOWARD CONSUMER PREFERENCES OF ISOTONIC DRINKING INSURABAYA - Achmad Daengs GS; Enny Istanti; Indriana Kristiwati (Journal of Managerial Sciences and Studies, 2026)
This study aims to examine the factors influencing consumer preferences for isotonic drinks in Surabaya. The independent variables include Product Quality, Price, Brand Image, Lifestyle, Packaging, and Promotion, while Consumer Preferences serve as the dependent variable. A quantitative survey approach was employed, involving 100 respondents selected through purposive sampling. Data were analyzed using multiple linear regression. The findings reveal that Product Quality, Price, Brand Image, Lifestyle, Packaging, and Promotion have positive and significant effects on Consumer Preferences, both individually and collectively. Among these variables, Product Quality emerged as the most dominant factor. The coefficient of determination (R²) of 0.809 indicates that 80.9% of the variation in Consumer Preferences is explained by the variables included in the model, while the remaining 19.1% is attributable to factors outside the scope of this study.